1994
DOI: 10.1002/stem.5530120308
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stimulation of neutrophil function by lenograstim (glycosylated rHug‐CSF) in oncohematologic patients: Results of a phase I trial

Abstract: Abstract. The aim of this work was to study the evolution of neutrophil functions in non-neutropenic cancer patients. Thirty non-neutropenic patients, median age 35 years (range 19-52), with solid tumors (n = 21) or lymphomas (n = 9) entered a phase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Previously, bactericidal activity and bacterial phagocytosis, as assessed by direct microscopy, were found to be significantly enhanced following pre‐incubation of normal PMN with G‐CSF ( Roilides et al , 1991 ). These results support the findings of a recent study investigating the in vivo stimulation of PMN function by G‐CSF in non‐neutropenic cancer patients ( Fossat et al , 1994 ). Circulating PMN from uraemic ESRF patients on CAPD show reduced phagocytosis and intercellular killing of S. epidermidis ( Harvey et al , 1987 , 1988).…”
Section: Discussionsupporting
confidence: 91%
“…Previously, bactericidal activity and bacterial phagocytosis, as assessed by direct microscopy, were found to be significantly enhanced following pre‐incubation of normal PMN with G‐CSF ( Roilides et al , 1991 ). These results support the findings of a recent study investigating the in vivo stimulation of PMN function by G‐CSF in non‐neutropenic cancer patients ( Fossat et al , 1994 ). Circulating PMN from uraemic ESRF patients on CAPD show reduced phagocytosis and intercellular killing of S. epidermidis ( Harvey et al , 1987 , 1988).…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence for differences between these three G‐CSF formulations in modifying neutrophil functions. Generally, chemotactic properties, which are essential for granulocyte function in host defense, are known to be impaired after treatment with G‐CSF 8‐12 . Azzara and coworkers 13 observed that filgrastim reduced chemotaxis more than lenograstim; recently published data attribute this reduced chemotaxis as well as morphological changes after filgrastim to cytoskeletal rearrangements 14 .…”
mentioning
confidence: 99%
“…Bacterial phagocytosis and bactericidal activity against Staphylococcus aureus have been found to be significantly enhanced after preincubation of normal PMN with G-CSF (Roilides et al, 1991). In addition, G-CSF has recently been reported to enhance the phagocytosis and bacterial killing of Staphylococcus aureus in non-neutropenic cancer patients (Fossat et al, 1994).…”
mentioning
confidence: 99%